2020
DOI: 10.1182/blood-2020-141286
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Outcomes of Patients with Post-Transplant Lymphoproliferative Disorder: A Single Center Retrospective Review

Abstract: Background Patients treated with chronic immunosuppression face a six-fold increase in their cumulative lifetime risk of lymphoma relative to age-matched immunocompetent counterparts. These malignances represent a spectrum of lymphoid and plasmacytic histologies collectively referred to as post-transplant lymphoproliferative disorders (PTLD). Accurate risk-stratification and optimal treatment strategies are unclear given wide histologic and clinical heterogeneity. Current standard-of-care models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…EBV reactivations are a main concern in transplant recipients, and EBV + PTLD is a life-threatening malignant complication following EBV reactivations. 4 Although our data now suggest that the occurrence of reactivation events is highly associated with the LMP-1 peptide variant of the infecting EBV strain, the question remains why some of these reactivating patients progress toward EBV + PTLD, whereas in others, the reactivation episode is limited. So far, the degree of immunosuppression, recipient age and ethnicity, allograft type, and distinct host genetic variations were considered as contributing to the risk for EBV + PTLD, 28 but cannot fully explain the progression toward this complication.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…EBV reactivations are a main concern in transplant recipients, and EBV + PTLD is a life-threatening malignant complication following EBV reactivations. 4 Although our data now suggest that the occurrence of reactivation events is highly associated with the LMP-1 peptide variant of the infecting EBV strain, the question remains why some of these reactivating patients progress toward EBV + PTLD, whereas in others, the reactivation episode is limited. So far, the degree of immunosuppression, recipient age and ethnicity, allograft type, and distinct host genetic variations were considered as contributing to the risk for EBV + PTLD, 28 but cannot fully explain the progression toward this complication.…”
Section: Discussionmentioning
confidence: 72%
“…EBV reactivations in transplant recipients may result in development of life-threatening EBV + PTLD. 4 We, therefore, assessed whether there is an association between host HLA-E and EBV LMP-1 peptide variants, EBV reactivation, and EBV + PTLD in transplant recipients. We included 180 EBV-polymerase chain reaction-positive patients after hematopoietic stem cell transplant (N = 31) or solid organ transplant (N = 149), who were followed up for 3 years after transplantation (Table 1).…”
Section: Hla-e Variants and Lmp-1 Peptide Ebv Reactivations In Transp...mentioning
confidence: 99%
See 1 more Smart Citation
“…These found a later onset, a higher ORR to treatment as well as a trend for a longer OS in the SOT group as compared to the allo-HSCT group. In contrast, the relapse rate was higher in the SOT as compared to the allo-HSCT group (24, 25,27,28). However, in most of these studies treatment is not comprehensively reported or patients from the prerituximab era are included.…”
Section: Discussionmentioning
confidence: 99%